Peg-tooth spacing and guide vane inclination of a Thai combine harvester affecting harvesting losses - Chuan-udom, Somchai; Thongsawatwong, Pinai; Saengprachatanarug, Khwantri; Eizo, Taira (Engineering and Applied Science Research, 2018)
Peg-tooth spacing and guide vane inclination of Thai combine harvesters are important parameters affecting harvesting losses. The harvester owners often adjust the peg-tooth spacing and guide vane inclination before harvesting. This study aimed to evaluate how harvesting loss are affected by the peg-tooth spacing and guide vane inclination of a Thai combine harvester. The results showed that increasing of peg-tooth spacing resulted in linearly increasing threshing unit loss. Threshing unit losses of Khao Dok Mali 105 (KDML 105) and Chainat 1 rice varieties were 0.0045 and 0.0306%/mm of spacing, respectively. Increasing of the guide vane inclination resulted in a linearly decreasing threshing unit loss. Threshing unit losses of KDML 105 and Chainat 1 rice varieties were 0.0575 and 0.3112%/degree of the guide vane, respectively.